Influence of tongue volume, oral cavity volume and their ratio on upper airway: A cone beam computed tomography study - S.S. Rana; O.P. Kharbanda; B. Agarwal (Elsevier, 2020)
Background: Our study aimed to measure the tongue volume (TV), oral cavity volume (OCV), and their ratio (TV/OCV) and correlate with upper airway using cone-beam computed tomography (CBCT). Method: The volume of oral cavity, tongue and upper airway were obtained by the manual process of segmentation of CBCT data of 15 subjects. The mean age of the sample was 21.86 years (range 15-33 years). Segmentation of the upper airway, tongue and oral cavity was performed manually using Mimics 11.0 (Materialise, Leuven, Belgium) software at different thresholds for air and the tongue. The Hounsfield units (HU) for airway volume of the different facial region ranged from −1024 to −500. For tongue volume, Hounsfield units (HU), ranging from −200 to 200 was calculated. Results: A significant negative correlation between TV/OCV and oropharynx (r = − 0.51; P = 0.04), TV/OCV and oral cavity airway volume (r = − 0.74; P = 0.002) was found. There was a significant and a positive correlation with TV/OCV and tongue volume (r = 0.65; P = 0.009). Conclusion: A significant negative correlation established between TV/OCV, oropharynx and oral cavity airway volume. This finding indicates an influence tongue volume, oral cavity volume and their ratio on patency of the oropharynx.